Endocrine disruptor hexachlorobenzene induces cell migration and invasion, and enhances aromatase expression levels in human endometrial stromal cells - Chiappini, Florencia; Ceballos, Leandro; Olivares, Carla; Bastón, Juan Ignacio; Miret, Noelia; Pontillo, Carolina; Zárate, Lorena; Singla, José Javier; Farina, Mariana; Meresman, Gabriela; Randi, Andrea (Food and chemical toxicology, 2022)
Endometriosis is the presence and growth of endometrial tissue outside of the uterus. Previous studies have suggested that endocrine disrupting chemicals such as organochlorine pesticides could be a risk factor for endometriosis. Hexachlorobenzene (HCB) is a weak ligand of the aryl hydrocarbon receptor (AhR) and promotes metalloproteinase and cyclooxygenase-2 (COX-2) expression, as well as, c-Src activation in human endometrial stromal cells (T-HESC) and in rat endometriosis model. Our aim was to evaluate the effect of HCB exposure on oestrogen receptor (ER) ɑ and β, progesterone receptor (PR) and aromatase expression, as well as, on cell migration and invasion in T-HESC and primary cultures of endometrial stromal cells from eutopic endometria of control subjects (ESC). Results show that HCB increases ERɑ and aromatase protein levels and reduces PR content in both T-HESC and ESC. However, the pesticide only increases ERβ expression in ESC, without changes in T-HESC. Moreover, cell migration and invasion are promoted by pesticide exposure involving the AhR, c-Src, COX-2 and ER pathways in T-HESC. HCB also triggers ERɑ activation via phosphorylation in Y537 through AhR/c-Src pathway. Our results provide experimental evidence that HCB induces alterations associated with endometriosis, suggesting that these mechanisms could contribute to pesticide exposure-induced endometriosis development. [Display omitted] •HCB increases ERɑ levels in T-HESC and ESC.•HCB enhances aromatase expression and reduces PR content in T-HESC and ESC.•HCB induces cell migration and invasion in T-HESC.•The increase in cell migration and invasion by pesticide is mediated by AhR, COX-2, ER and c-Src.•HCB promotes ERɑ phosphorylation in Tyr-537 through AhR/c-Src axis in T-HESC.